Benchmark rate risk, duration gap and stress testing in dual banking systems - Chattha, Jamshaid Anwar; Syed Jaafar Alhabshi, Syed Musa (Elsevier B.V., 2020)
Islamic commercial banks (ICBs) deal with a variety of risks, a pressing one being benchmark rates risk or rate of return risk (ROR). The purpose of this study is to measure the impact of changing benchmark rates on the net worth (NW) risk (i.e. economic value) of ICBs and conventional commercial banks (CCBs), with duration gap and stress testing approaches, in dual banking systems with a sample of 100 commercial banks (50 ICBs and 50 CCBs) from 13 countries, for the period 2009–2015. The study provides empirical evidence regarding the estimation and determination of duration gap. In particular, with regards to NW risk for increasing benchmark rate, we found that the ICBs are 2.15 times more vulnerable compared to the CCBs, and a significant number of the ICBs failed the stress test of the 20% threshold prescribed by the IFSB. As a result of higher duration gap, the ICBs are vulnerable to a significant loss of NW under an increasing benchmark rate regime in dual banking systems. The study makes profound contributions to the literature and suggests various policy recommendations including identifying and measuring the significance of the duration gap and NW risk, and having in place Sharī'ah-compliant hedging techniques to manage the increasing rate changes